2018
DOI: 10.20944/preprints201810.0477.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Processing of Thermoplastic PLA/Cellulose Nanomaterials Composites

Abstract: Over the past decades, research has escalated on the use of polylactic acid (PLA) as replacement for petroleum-based polymers. This is due to its valuable properties, such as renewability, biodegradability, biocompatibility and good thermomechanical properties. Despite possessing good mechanical properties comparable to conventional petroleum-based polymers, PLA suffers from some shortcomings such as low thermal resistance, heat distortion temperature and rate of crystallization, thus different fillers have be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 76 publications
0
17
0
2
Order By: Relevance
“…Since the mechanical properties of composites are essential in material selection, a possible addition with reinforcing properties for both PLA and PHA matrices are cellulose nanoparticles. Several studies reported that the use of cellulose nanocrystals (CNC) in PLA matrices increased the tensile strength [ 13 , 14 ], whereas the addition of CNC in PHA leads to limited reinforcement [ 15 , 16 ]. Besides the improved mechanical properties of the PLA matrices, CNC exhibit singular structural features and excellent physicochemical properties such as biocompatibility, biodegradability, renewability, low density, adaptable surface chemistry, and optical transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mechanical properties of composites are essential in material selection, a possible addition with reinforcing properties for both PLA and PHA matrices are cellulose nanoparticles. Several studies reported that the use of cellulose nanocrystals (CNC) in PLA matrices increased the tensile strength [ 13 , 14 ], whereas the addition of CNC in PHA leads to limited reinforcement [ 15 , 16 ]. Besides the improved mechanical properties of the PLA matrices, CNC exhibit singular structural features and excellent physicochemical properties such as biocompatibility, biodegradability, renewability, low density, adaptable surface chemistry, and optical transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanomaterials are cost-effective, renewable, thermally stable up to 200 °C, and lightweight and provide high strength and stiffness. As a biomaterial of anisotropic shape, good biocompatibility, excellent mechanical properties, and tailorable surface chemistry, it is of high interest for material science and biomedical engineering (wound dressing, nanocarriers for drug delivery, and scaffolds for tissue engineering) [ 73 , 74 , 75 , 76 ]. Nanocellulose of defined nano-scale structural dimensions is derived from cellulosic extracts or processed materials.…”
Section: Pla/nanocellulose Compositesmentioning
confidence: 99%
“…They observed the improvement of the storage modulus and heat distortion temperature of PLA. Teboho C. Mokhena et al [ 21 ] overviewed preparation and processing methods, and the mechanical, dynamic mechanical and thermal properties of PLA reinforced with cellulose nanomaterials (cellulose nanocrystals and cellulose nanofibers) (the citation number: 25). This type of material is known as “green composites”, which are of increasing concern due to their sustainability.…”
Section: Category (2): Environmentally Benign Polymersmentioning
confidence: 99%